Multisystem thromboembolism in a COVID-19 patient: a case report - Moaaz Baghal; Viralkumar Amrutiya; Swati Govil; Rutwik Patel; Mark Gabelman; Brandon Gaynor; Syed Jafri; Abraham Lo (Greater Baltimore Medical Center, 2021)
Hypercoagulability has been found in patients diagnosed with the novel coronavirus 19 (COVID-19) and has been identified as a major cause of morbidity and mortality. Herein, we report the challenge in managing a patient presenting with a 5 day history of COVID-19 diagnosis, complicated by deep venous thrombosis, pulmonary embolism and ischemic stroke in the setting of atrial septal aneurysm, presumed patent foramen ovale and paradoxical embolism, identified to have clots in transit on echocardiogram. The application of anticoagulation was felt to be high risk. The patient was transferred to a tertiary facility where the patient underwent thrombus aspiration and was eventually complicated by hemorrhagic conversion of the stroke.